Histological grading in lung cancer: one system for all or separate systems for each histological type?. Issue 3 (March 2016) - Travis, William D.; Brambilla, Elisabeth; Geisinger, Kim R.
The grading of cancer is a histological method intended to help predict prognosis based on specific morphological features. It typically is based on architectural or cytological features (nuclear grade or number of mitoses), or in some cases, a combination of both. Grading is usually broken down into a spectrum from well differentiated (grade 1) to the most poorly differentiated (grade 3 or 4). The number of grades ranges from two to five [1–3]. The highest grade tumours (grade 3 or 4) lack any specific differentiation. The morphological criteria for grading usually differ from that used in histological classification, but in some systems, histological classification is a major component of grade. Two recent studies show the importance of tumour budding and nest size in grading of lung squamous cell carcinoma http://ow.ly/WTaQ2